2015
DOI: 10.4081/gh.2015.376
|View full text |Cite
|
Sign up to set email alerts
|

Space-time clustering characteristics of dengue based on ecological, socio-economic and demographic factors in northern Sri Lanka

Abstract: The aim of the present study was to identify geographical areas and time periods of potential clusters of dengue cases based on ecological, socio-economic and demographic factors in northern Sri Lanka from January 2010 to December 2013. Remote sensing (RS) was used to develop an index comprising rainfall, humidity and temperature data. Remote sensing data gathered by the AVNIR-2 instrument onboard the ALOS satellite were used to detect urbanisation, and a digital land cover map was used to extract land cover i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 19 publications
(26 reference statements)
1
11
0
1
Order By: Relevance
“…It showed the significant spatiotemporal variation pattern of DF in the study area. Our finding is in line with other studies of space time scan statistic of DF carried out by Dhewantara et al in Indonesia (12) , Anno et al in Sri Lanka (13) , Chuang et al in Taiwan (20) , Acharya et al in Nepal (21) , and Hamer et al in Suriname (22) confirmed that DF cases tend to cluster.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…It showed the significant spatiotemporal variation pattern of DF in the study area. Our finding is in line with other studies of space time scan statistic of DF carried out by Dhewantara et al in Indonesia (12) , Anno et al in Sri Lanka (13) , Chuang et al in Taiwan (20) , Acharya et al in Nepal (21) , and Hamer et al in Suriname (22) confirmed that DF cases tend to cluster.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, these approaches are useful for prioritizing DF surveillance and vector control. (12,13) Therefore, it is needed to discover the distribution pattern of DF cases and determine the spread of the disease spatially in Medan Municipality. This study aimed to investigate the presence of DF clusters in Medan Municipality and the temporal distribution pattern of detected such cluster over the four years.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Sri Lanka reported an infection rate of per people, and approximately a quarter of notified cases occurred in children under years old living in dengue transmission areas 16 . And since the early 2000s, progressively larger epidemics in Sri Lanka have occurred every regular period of time and increased in magnitude and frequency 17 . In urban areas, the disease incidence is the highest, especially in the district of Colombo, the most densely populated part of the country 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Applications of spatial technologies for malaria transmission modeling and control were reviewed in 2015 by Gebreslasie [ 48 ]. In addition to malaria [ 8 - 10 , 17 , 24 , 26 , 31 , 33 - 35 , 38 - 42 , 46 , 48 , 49 , 55 , 56 , 76 , 87 , 90 - 93 , 99 , 100 , 102 , 103 , 105 , 111 - 115 , 118 , 119 , 122 , 129 - 132 , 141 ] and schistosomiasis [ 15 , 37 , 53 , 54 , 63 , 95 , 124 , 126 , 127 , 142 - 145 , 153 , 154 , 156 , 158 ], dengue fever [ 7 , 12 , 13 , 16 , 23 , 44 , 89 , 94 , 98 , 101 , 117 , 140 ], cholera [ 43 , 71 , 72 , 74 , 75 ,…”
Section: Resultsmentioning
confidence: 99%